2011
DOI: 10.1590/s0074-02762011000500018
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of two Neisseria gonorrhoeae fluroquinolone-resistant strains in the Brazilian Amazon Region

Abstract: (S91F and D95G in GyrA and S87R in ParC). Both isolates were genotyped using N. gonorrhoeae multi-antigen sequence typing and the analysis showed that the ST225 which represented an emerging widespread multi-resistant clone that has also been associated with reduced susceptibility to ceftriaxone. We recommend continued surveillance of this pathogen to assess the efficacy of anti-gonococcal antibiotics in Brazil.Key words: Neisseria gonorrhoeae -fluroquinolone resistance -gyrA and parC -genotyping -MAST Two ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
3
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
2
3
0
1
Order By: Relevance
“…The reduction of the resistance of gonococci to both antibiotics may have been the result of some associated factors as follows: those antibiotics are not used at STD clinic in FUAM anymore; governmental measures rule the antibiotic market and the recommendations of standard guidelines (13) to use different kinds of antimicrobials to treat gonorrhea. Regarding quinolones, our findings confirm the presence of resistant gonococci in the region (14) , but the frequency of resistance detected does not preclude their usage DOI: 10.5533/DST-2177-8264-2015271-211 in therapy. There was no resistance to ceftriaxone in this study, but it is noteworthy that gonococcus with reduced sensitivity to this antibiotic (15) (MIC of 0.064 µg/mL) had been reported in the region before (14) .…”
Section: Notesupporting
confidence: 51%
See 1 more Smart Citation
“…The reduction of the resistance of gonococci to both antibiotics may have been the result of some associated factors as follows: those antibiotics are not used at STD clinic in FUAM anymore; governmental measures rule the antibiotic market and the recommendations of standard guidelines (13) to use different kinds of antimicrobials to treat gonorrhea. Regarding quinolones, our findings confirm the presence of resistant gonococci in the region (14) , but the frequency of resistance detected does not preclude their usage DOI: 10.5533/DST-2177-8264-2015271-211 in therapy. There was no resistance to ceftriaxone in this study, but it is noteworthy that gonococcus with reduced sensitivity to this antibiotic (15) (MIC of 0.064 µg/mL) had been reported in the region before (14) .…”
Section: Notesupporting
confidence: 51%
“…Regarding quinolones, our findings confirm the presence of resistant gonococci in the region (14) , but the frequency of resistance detected does not preclude their usage DOI: 10.5533/DST-2177-8264-2015271-211 in therapy. There was no resistance to ceftriaxone in this study, but it is noteworthy that gonococcus with reduced sensitivity to this antibiotic (15) (MIC of 0.064 µg/mL) had been reported in the region before (14) . Concerning azithromycin, the frequency of 1.2% of resistance enables the use of this antibiotic as a therapeutic option at the currently recommended dose (5) if necessary.…”
Section: Notesupporting
confidence: 51%
“…Ciprofl oxacin resistance is greatly increased (21.4%) compared to other national studies. These studies initially observed decreased susceptibility 19,21 followed by drug resistance in Manaus 23 27 (47.7%), have detected high levels of resistance to ciprofl oxacin, and thus its use for the treatment of gonorrhea has been discontinued in these locations 4,32,33 . In addition, specimens with a high level of resistance to ciprofl oxacin (MIC>32µg/ml) that also exhibited resistance to chloramphenicol and tetracycline were identifi ed.…”
mentioning
confidence: 99%
“…Spectinomycin exhibits excellent sensitivity, but it is only effective for urethral and rectal infections 33 . However, Pharyngeal (P) infections are asymptomatic, and although increasing in importance 6,7 , particularly in the MSM population, this site is rarely screened.…”
mentioning
confidence: 99%
See 1 more Smart Citation